A thermo-elastic-plastic phase-field model for simulating the evolution and transition of adiabatic shear band. Part II. Dynamic collapse of thick-walled cylinder. (15th May 2020) - Wang, T.; Liu, Z.L.; Cui, Y.N.; Ye, X.; Liu, X.M.; Tian, R.; Zhuang, Z.
Highlights: The self-organization of ASB is studied by thermo-elastic-plastic phase-field model. The contribution of thermal softening to ASB is less than that of damage softening. Large defects play a dominant role in the initiation and evolution of ASBs. Abstract: In Part I, a thermo-elastic-plastic phase-field model is established for describing the adiabatic shear band (ASB) in metal materials. In this Part II, the developed model is used to simulate the classical thick-walled cylinder (TWC) experiment to investigate the self-organizing behavior of multiple ASBs. For the first time, the formation process of self-organized ASBs in the TWC experiment is reproduced by the phase-field method and the underlying physical mechanism is analyzed in detail. The simulation results show that the number and spacing of ASBs are related to loading rate and material properties. A higher loading rate leads to more intensive ASBs. For typical engineering materials such as 304L stainless steel (Ss304L) and titanium alloy (Ti6Al4V), the contribution of thermal softening to the formation of ASBs is far less than that of damage softening. However, thermal softening is very important to induce initial ASBs. In addition, we also find that defects, especially large ones, play a dominant role in the initiation and evolution of ASBs, leading to complex patterns of ASBs in the TWC experiments.